Draft Eleventh Five Year Plan (2007-12) and Annual Plan 2007-08 Volume 2 Government of Assam - Planning Commission (Planning Commission, 2007)
Agriculture plays a vital role in the economy of Assam contributing 28.84.percent to the Net State Domestic product in 2005-06 at current prices (quick estimate). The state of Assam comprising 24 numbers of plain districts and 2 numbers of hill districts fall under high potential zone for raising agricultural productivity. Assam is basically an agrarian state with more than 70 percent of its population ( 2.66 crores as per 2001 census) taking to agricultural practices either fully or partially. Out of the total geographical area of 78.44 lakh hectares, almost one third (31.74 percent) is under net cultivation covering an area of 24.90 lakh hectares. The gross cropped area occupies about 38.43 lakh hectares.
Government of Assam Planning and Development Department Dispur